Design and analysis of multi‐stage PID controller for frequency control in an islanded micro‐grid using a novel hybrid whale optimization‐pattern search algorithm - Khadanga, Rajendra Kumar; Padhy, Sasmita; Panda, Sidhartha; Kumar, Amit (International journal of numerical modelling, 2018)
In this research work, a maiden approach is made for the frequency control in an islanded AC Microgrid (MG) by considering a hybrid Whale Optimization Algorithm and Pattern Search (hWOA‐PS) algorithm based multi‐stage Proportional Integrator Derivative controller. A MG may be formed by combining some of the unique assets like renewable energy sources, wind electricity era, and the sun electricity irradiation. Variation in any of the source influences the system frequency, and thus frequency control issue in MG is always a challenge for the researchers. In light of these difficulties, this paper considers a multi‐stage PID controller for the secondary frequency control of the islanded MGs, and a novel hWOA‐PS algorithm is used to tune the controller parameters. The proposed hybrid controller is inspected on a MG test system, and the robustness and execution are assessed by considering different disturbances and parametric variations. In order to show the effectiveness of the proposed hybrid algorithm based multi‐stage Proportional Integrator Derivative controller, it is being compared with some conventional controllers like Integral (I), Proportional Integral (PI), and Proportional Integral and Derivative (PID) controller.